Public Perception of Earthquake and Tsunami Disaster Management in Tanjung Padang Village, Sirenja District, Donggala Regency - Poniman Poniman; Ince Rahmi; Helvie Etma Wati Gae; Ani Maryani; Zhanaz Tasya; Budiman Budiman (PT. Anagata Sembagi Education, 2025)
This study aims to explore the perceptions of the Tanjung Padang Village community, Sirenja District, Donggala Regency, regarding earthquake and tsunami disaster management. A qualitative approach was used, using the Focus Group Discussion (FGD) method, involving 10 participants, including the Village Head, Hamlet Head, Posyandu (Integrated Service Post) cadres, LPM (LPM) members, community leaders, and village midwives. The results show that community perceptions of disasters vary, with most viewing them as fate, while others are beginning to understand the importance of mitigation. Technical knowledge related to disaster preparedness is still limited, and an adequate early warning system is not yet available. However, the community showed high enthusiasm for participating in disaster training and has social potential in the form of mutual cooperation that can be developed as a local strength. This study highlights the importance of community involvement and strengthening local capacity in community-based disaster management.